Lung carcinoma after radiation therapy in women treated with lumpectomy or mastectomy for primary breast carcinoma - Lydia B. Zablotska; Alfred I. Neugut (2003)
Prior studies have demonstrated that women who receive adjuvant radiation therapy (RT) after mastectomy for breast carcinoma have an increased risk of a second primary lung carcinoma after 10 years, but, to the authors' knowledge, the risk associated with adjuvant RT after breast-conserving surgery (lumpectomy) has yet to be determined. The purpose of the current study was to confirm and extend earlier findings of the effects of postmastectomy RT on second primary lung carcinoma and to investigate the impact of postlumpectomy RT on second primary lung carcinoma in the same population and to compare the results.The authors used data from the population-based Surveillance, Epidemiology, and End Results (SEER) program of the U.S. National Cancer Institute, encompassing approximately 10% of the U.S. population, from 1973 to 1998. Of the women with nonmetastatic invasive breast carcinoma, 194,981 had been treated with mastectomy and 65,560 were treated with lumpectomy. Cox regression analysis was used to estimate the relative risk (RR) of a second primary lung carcinoma among women treated with RT compared with those who received surgery alone as a function of time interval since treatment and laterality for both types of surgery.Although no statistically significant elevation in risk for second primary lung carcinoma prior to 10 years was observed, the authors estimated a RR of 2.06 (95% confidence interval [95% CI], 1.53-2.78) and 2.09 (95% CI, 1.50-2.90) for ipsilateral lung carcinoma at 10-14 years and 15+ years after postmastectomy RT, respectively, whereas no increased risk was observed for the contralateral lung. The excess risk of ipsilateral lung carcinoma after postmastectomy RT was found for all three major histologic subtypes of lung carcinoma (adenocarcinoma, squamous cell carcinoma, and small cell carcinoma). No increased risk of lung carcinoma was observed at 10-14 years after postlumpectomy RT for either lung.Postmastectomy RT was found to provide a moderate increase in risk for ipsilateral lung carcinoma starting 10 years after exposure; this increased risk is reported to persist to at least 20 years. Postlumpectomy RT does not appear to incur an increased risk. These findings should be reassuring to women treated with either type of RT, but the excess risk in the postmastectomy group should be considered in the choice between treatment options.